Addition of Autologous Mesenchymal Stem Cells to Whole Blood for Bioenhanced ACL Repair Has No Benefit in the Porcine Model. (February 2015) - Proffen, Benedikt L.; Vavken, Patrick; Haslauer, Carla M.; Fleming, Braden C.; Harris, Chad E.; Machan, Jason T.; Murray, Martha M.
Background: Coculture of mesenchymal stem cells (MSCs) from the retropatellar fat pad and peripheral blood has been shown to stimulate anterior cruciate ligament (ACL) fibroblast proliferation and collagen production in vitro. Current techniques of bioenhanced ACL repair in animal studies involve adding a biologic scaffold, in this case an extracellular matrix–based scaffold saturated with autologous whole blood, to a simple suture repair of the ligament. Whether the enrichment of whole blood with MSCs would further improve the in vivo results of bioenhanced ACL repair was investigated. Hypothesis: The addition of MSCs derived from adipose tissue or peripheral blood to the blood–extracellular matrix composite, which is used in bioenhanced ACL repair to stimulate healing, would improve the biomechanical properties of a bioenhanced ACL repair after 15 weeks of healing. Study Design: Controlled laboratory study. Methods: Twenty-four adolescent Yucatan mini-pigs underwent ACL transection followed by (1) bioenhanced ACL repair, (2) bioenhanced ACL repair with the addition of autologous adipose-derived MSCs, and (3) bioenhanced ACL repair with the addition of autologous peripheral blood derived MSCs. After 15 weeks of healing, the structural properties of the ACL (yield load, failure load, and linear stiffness) were measured. Cell and vascular density were measured in the repaired ACL via histology, and its tissue structure was qualitatively evaluated using the advanced Ligament Maturity Index. Results: After 15 weeks of healing, there were no significant improvements in the biomechanical or histological properties with the addition of adipose-derived MSCs. The only significant change with the addition of peripheral blood MSCs was an increase in knee anteroposterior laxity when measured at 30° of flexion. Conclusion: These findings suggest that the addition of adipose or peripheral blood MSCs to whole blood before saturation of an extracellular matrix carrier with the blood did not improve the functional results of bioenhanced ACL repair after 15 weeks of healing in the pig model. Clinical Relevance: Whole blood represents a practical biologic additive to ligament repair, and any other additive (including stem cells) should be demonstrated to be superior to this baseline before clinical use is considered.